2010
DOI: 10.1111/j.1464-5491.2010.03032.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived risk of Type 2 diabetes in Australian women with a recent history of gestational diabetes mellitus

Abstract: Although women with known risk factors for Type 2 diabetes were more likely to perceive their risk as high, we found that one third still considered themselves to be at low or very low risk for the development of diabetes. These results suggest a need for increased awareness of gestational diabetes as a strong predictor of Type 2 diabetes risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
46
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 15 publications
12
46
1
Order By: Relevance
“…While prior survey-based studies in the United States and Australia have shown that few women with GDM perceive high risk for T2DM [14,37], findings from qualitative studies have been more mixed; some of the variability may relate to the population studied and proximity to delivery [16,17,38]. Similar to prior studies, women in our study linked their risk for T2DM to presence or absence of family history of T2DM, their weight status, and current health habits [14,39].…”
Section: Discussionsupporting
confidence: 82%
“…While prior survey-based studies in the United States and Australia have shown that few women with GDM perceive high risk for T2DM [14,37], findings from qualitative studies have been more mixed; some of the variability may relate to the population studied and proximity to delivery [16,17,38]. Similar to prior studies, women in our study linked their risk for T2DM to presence or absence of family history of T2DM, their weight status, and current health habits [14,39].…”
Section: Discussionsupporting
confidence: 82%
“…First, our cohort was motivated to participate in our study and thus may not be representative of other populations who have GDM. Indeed, previous studies suggest that diabetes risk perception is low in women with prior GDM (42,49). In addition, all of our participants were English speaking, and the majority had high income, were highly educated, and were living with a spouse or partner; thus, they may not be representative of women with lower incomes and/or education levels.…”
Section: Discussionmentioning
confidence: 92%
“…First, a self-administered written questionnaire and second, a telephone interview conducted in parallel by trained interviewers using Computer-Assisted-Telephone-Interviewing for Windows (WinCati, Version 4.2; Sawtooth Technologies, Northbrook, IL, USA); full details of which have been described elsewhere. 6,20 Briefly, the survey questions addressed demographics, educational attainment, language spoken at home and occupation using standard items from the 2001 Australian census. 21 Information regarding GDM management, lifestyle-related risk factors, family and medical history, and postpartum follow-up were collected by self-report.…”
Section: Survey Designmentioning
confidence: 99%